Critical Discourse Analysis (CDA) of the bolivian representation in the chilean nationwide daily press news. The case of the newspapers El Mercurio and La Tercera (Polis (Santiago), 2018)
In the dialogues among the different voices that appear in the communication media there is an unequal share and it is possible to see that preponderance is given to some social actors declining others. Such relationship becomes even more complex when participants belong to different cultures. The following research intends, through a methodological tool related to the Critical Discourse Analysis (CDA) developed by Teun van Dijk, to unveil the processes and representation forms with which the bolivians are looked upon, on the news of nationwide newspapers El Mercurio and La Tercera, during the month of june 2008. The study, therefore, sets up to reveal how the written press collaborates with the representation and construction of intercultural reality (Berger y Luckmann, 1972) of its readers, setting up and promoting sociocultural prejudices and stereotypes.
Keywords: Bolivia-Chile; intercultural journalism; critical discourse analysis (CDA); social construction of reality